Analisis Tindak Tutur Direktif Tayangan “Si Bolang” di Youtube Edutainment Trans 7 Official dan Rekomendasinya Sebagai Bahan Ajar pada Teks Laporan Percobaan di Kelas IX - Wiratama, Aditya Dwi; Muhtarom, Imam; Syafroni, Roni Nugraha (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research uses speech act theory according to Prayitno (2011:41) that directive speech acts do not only function to inform something. Directive speech acts have a very important role in everyday communication and are used to achieve various goals in social interactions. The research carried out was related to the analysis of directive speech acts in the "Si Bolang" broadcast on the Edutainment Trans7 Official YouTube channel. With a total of four "Si Bolang" video views on the Trans7 Official Edutainment YouTube channel. Utilization of research results of analysis of directive speech acts in the "Si Bolang" broadcast for junior high school level Indonesian language learning as teaching material for handouts of experimental report text material. With the basic competencies and core competencies of the 2013 curriculum found in class IX odd semester. The results of this research show what forms of directive speech acts and speech act strategies are used in broadcasts. This research uses descriptive qualitative research to analyze the object of study of directive speech in the show "Si Bolang". This research uses a qualitative research approach. The results of this research focus on analyzing the form of directive speech acts and strategies for directive speech acts. The form of directive speech acts has six forms, namely, commands, invitations, advice, prohibitions, criticism and requests. Meanwhile, there are two types of directive speech act strategies, direct speech act strategies and indirect speech act strategies. The results of the analysis contained 139 data (commands), 22 data (invitations), 4 (advice), 2 data (prohibitions), 2 data (criticism) and 12 data (requests). There are two strategies for directive speech acts in the research, namely direct speech act strategies, there are 170 data, and indirect speech act strategies, there are 11 data.